Effects of Fluid Gelatin for Lumbar Spinal Stenosis Undergoing Lumbar Endoscopic Bilateral Decompression: A Prospective, Randomized Controlled Trial - Hao Yan; Mingdong Yu; Huaibin Wang; Rongsheng Dou; Xiaoyan Xia; Ruzhan Yao; Weiqiang Liu; Jesse Li‐Ling (Orthopaedic Surgery)
ABSTRACT Objectives In patients with lumbar spinal stenosis (LSS), prolonged compression of the epidural venous plexus heightens the risk of bleeding and hematoma during minimally invasive surgery. While absorbable fluid gelatin, an animal protein–based hemostatic agent, is available, its effectiveness in lumbar endoscopic unilateral laminotomy with bilateral decompression (LE‐ULBD) remains debated. Our research aims to conduct a prospective randomized controlled trial to investigate the effectiveness and safety of this hemostatic material in patients undergoing LE‐ULBD for LSS. Methods From October 2023 to July 2024, a total of 90 patients with LSS who underwent LE‐ULBD were enrolled in this study. The 90 patients were randomly divided into two groups: fluid gelatin group (45 cases, using fluid gelatin) and null‐fluid gelatin group (45 cases, not using fluid gelatin). Primary outcomes included the success rate of achieving hemostasis within 3 min and symptomatic postoperative epidural hematoma (SPEH). Secondary outcomes encompassed surgical time, intraoperative blood loss, perioperative blood loss, length of stay, and complications. Independent sample t tests were used to compare continuous data. Chi‐squared tests and Fisher's exact probability tests were used to analyze the categorical data. Results The success rate of achieving hemostasis within 3 min (p < 0.05) was significantly higher in fluid gelatin group compared to that in the null‐fluid gelatin group, and perioperative blood loss (p < 0.05) and surgical time (p < 0.05) were notably lower in the fluid gelatin group. However, there were no statistically significant differences between the two groups regarding intraoperative blood loss, length of stay, and complications, such as SPEH, allergy, and thrombus. Conclusion In patients with LSS undergoing LE‐ULBD surgery, using fluid gelatin can achieve rapid intraoperative hemostasis, shorten surgical time, and reduce perioperative blood loss without causing complications. Therefore, the conventional use of fluid gelatin in LE‐ULBD surgery is an effective and safe strategy.